2017
DOI: 10.4336/2017.pfb.37.89.1280
|View full text |Cite
|
Sign up to set email alerts
|

Crescimento inicial de plantas de pequi após aplicação de 2,4-D

Abstract: Resumo -O ácido 2,4-diclorafenóxacético (2,4-D) tem causado efeitos tóxicos em várias culturas cultivadas vizinhas ao local na qual foi destinado, devido à deriva durante sua aplicação. Objetivou-se, nesta pesquisa, avaliar o efeito da deriva simulada por meio de subdoses do herbicida 2,4-D em plantas de pequi (Caryocar brasiliense, Camb.). Testaram-se em blocos completos casualizados com seis repetições as doses de 0; 1, 67; 3,35; 6,70; 16,75; 33,50; 67,00 e 134,00 g ha -1 de equivalente ácido do herbicida. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 22 publications
(18 reference statements)
1
7
0
3
Order By: Relevance
“…Polini et al (2018) evaluated the selectivity of herbicides in native forest species of the Cerrado biome and concluded that herbicide imazapyr, when applied at low doses in post-emergence, is selective for tree species Schinus terebinthifolia, Peltophorum dubium, and Handroanthus albus; at high concentrations, however, it may affect their survival differently. Tavares et al (2017) observed that the initial growth of Caryocar brasiliense plants was benefited from the application of 2,4-D subdoses for the variables leaf area, specific leaf area, and leaf area ratio. However, with increasing doses, there was a reduction in seedling growth, characterized by a decrease in leaf variables and in the total dry weight of plants.…”
Section: Resultsmentioning
confidence: 99%
“…Polini et al (2018) evaluated the selectivity of herbicides in native forest species of the Cerrado biome and concluded that herbicide imazapyr, when applied at low doses in post-emergence, is selective for tree species Schinus terebinthifolia, Peltophorum dubium, and Handroanthus albus; at high concentrations, however, it may affect their survival differently. Tavares et al (2017) observed that the initial growth of Caryocar brasiliense plants was benefited from the application of 2,4-D subdoses for the variables leaf area, specific leaf area, and leaf area ratio. However, with increasing doses, there was a reduction in seedling growth, characterized by a decrease in leaf variables and in the total dry weight of plants.…”
Section: Resultsmentioning
confidence: 99%
“…Known as a growth regulator, synthetic auxin or hormonal herbicide, 2,4-D belongs to the class of auxin-mimicking herbicides, because at low concentrations it has physiological and biochemical effects similar to those of the indole-3-acetic acid (IAA), the main natural auxin present in plants (Vanneste and Friml, 2009). Thus, it is expected that the hormesis effect of the 2,4-D herbicide may cause an increase of auxins production and activity, with adverse impacts on the plant's growth and development (Tavares et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Auxin-based herbicides, such as 2,4-D, are examples of chemicals that enhance growth at nontoxic concentrations but are lethal at higher rates (Americo et al, 2017). Thus, such responses may be expected with increased auxins production and activity and may interfere with the plants' growth and development (Tavares et al, 2017).…”
Section: Introductionmentioning
confidence: 99%